Elemental Symbolism and Character Relationships in Elemental Forces of Nature: A Semiotic Approach - Erina Tri Oktaviana; Abdillah Nugroho (Journal of English Language Teaching and Literature)
The purpose of this study is to see how human figures are shown by the symbolism of the elements and how the interaction between the elements can cause semiotic phenomena rooted in the concept of the basic elements of the earth, namely fire, water, earth and air. This is to analyze whether the product is reflected in this way. Using the semiotic theory of Perce and Barthes, this study seeks to identify the implications and negative meanings of the elements of human personality. This study uses a qualitative approach in a case study design. Data were collected in depth about film scenes that show the interaction between elements and human characters. The data collection process was carried out through participant observation methods, theme notes, and symbolic analysis of visual and narrative elements. Data analysis techniques are related to the structural semiotic model which includes identifying signs, determining meaning, and interpreting symbolic relationships in a historical context. The results of the study show that 30 data show the relationship between natural elements with specific semiotic meanings and human personality. The fire element is often connected to characters who are passionate about being ambitious and easily ignited by their emotions, while the water element represents calmness, adaptability, and empathy. The earth element represents stability, determination, and maturity, while the air element reflects freedom, intelligence, and imagination. The interaction between these film elements not only shows the social dynamics of the characters, but also reflects the idea of ​​balance and conflict in human life. The contribution of this study is to provide a deeper understanding of the role of elemental symbolism in character formation in visual media.